Preparation and characterization of supported ionic liquid membrane based on [EMIM][TFSI]/non-solvent/NMP/PSF for gas separation - Tang, Georgina YanJie. (2013)
As the world becomes more concerned about environmental issues, industries have been continuously researching on safe and environmentally friendly alternatives. Ionic liquids have been widely reported as ‘green’ solvents due to their unique properties such as negligible vapour pressure. Hence, the application of ionic liquid for gas separation has been widely studied in the recent years.